Analysis of key competences in vocational education - Василь Стрюков; Олена Громцева (Social Development & Security, 2019)
Modern vocational education is considered as a mechanism for managing the development of a competitive personality, its individual capabilities, socio-cultural, socio-moral and professional qualities and abilities that the future specialist needs to advance to be professional. The purpose of the article is to review the key competencies which pursued in vocational educational institution students. The study used a set of methods: study and analysis of literary sources on the problem of research, analysis, generalization and systematization of theoretical data. The article summarizes the content of such concepts as «competence», «competency», «competence approach», «professional competence» and «professionalism». The peculiarities of forming and comparing the components of professional competence of future specialists of different specialties (teachers, managers) are analyzed. In the process of theoretical data of groups of skills, knowledge and individual competences systematization there are four types of professional competence – special, social, personal and individual, while the components of professional competence have a similar structure, but differ significantly. This is due to the fact that certain activities include different components. The way of formation of professional competence in students from choice of specialty and educational institution to professional skill is analyzed. The results of the study helped to clarify the essence of professional competence, which is an integrated concept that combines the most important professional competencies. The choice of a profession and the formation of professional abilities are only truly successful when they are connected with the social and moral choice of a young person, which is reflected in the text of the article. A deep reform of the national education system is underway in Ukraine and there is a constant modernization of technological production processes. Against this background, it is advisable to focus further research on the continuous updating and improvement of the components of professional competence. Formation of the list of professional competences is a prerequisite for the training of specialists at the present stage. Prospects for further scientific research of the authors are to find and update the economic and organizational mechanisms of competence management in vocational education.